Work-related musculoskeletal disorders (WMSDs) among teachers and student's management assistants in special education schools in Malaysia / Yanusiya Argenan - Yanusiya, Argenan (2017)
A student with Special Educational Needs (SEN) requires more attention and assistance in school compared to peers of their age. Teachers and Student’s Management Assistants (SMAs) in these schools will have to be highly responsible for meeting the students’ daily needs which results in symptoms of musculoskeletal systems. In conjunction with this issue, the objectives of this study are to determine of risk factors that lead to Work- Related Musculoskeletal Disorders (WMSDs) on educators at school and to suggest on ways to overcome the disorder as preventive measures for higher productivity at work. Questionnaires consisting of personal information, job specification and work-related information were distributed in 5 Special Education Schools. This study shows 96.23%prevalence rate meaning that WMSDs occurs in 9 out of 10 teachers and Student’s Management Assistant. The most affected regions were upper back with 90.6% (n=48), lower back with 81.1% (n=43), knee with 67.9% (n=36) and shoulder with 47.2% (n=25). Results show that there are multiple risk factors that lead to WMSDs among teacher and Student’s Management Assistant at Special Education Schools. Risk factors at work (such as the work-related risk factors and individual-related risk factors) were determined and suggestion on ways to overcome WMSDs as preventive measures relating to engineering, administrative control and application of ergonomics for high productivity at work were included in this study to decrease number of injuries and prevent WMSDs at work. The study recommends thatthe effort of teachers and Student’s Management Assistant to apply safe working practice should be encouraged by the school management and Ministry of Education Malaysia to prevent WMSDs.